Pengaruh pertumbuhan ekonomi, tingkat kemiskinan, pengeluaran pemerintah, tingkat pengangguran terbuka terhadap Indeks Pembangunan Manusia (IPM) Provinsi-provinsi di Sumatera - Dzaki Furqoni ZA; Junaidi Junaidi; Adi Bhakti (Konsentrasi Ekonomi Sumberdaya Alam dan Manusia, Prodi Ekonomi Pembangunan, Fakultas Ekonomi dan Bisnis, Universitas Jambi, 2019)
Study are as follows: To analyze the effect of economic growth, poverty level, government expenditure and open unemployment on the Human Development Index (HDI) of the Provincial Provinces in Sumatra for the period 2013-2017. Based on the results of the study that economic growth has a significant effect on the human development index. Poverty level has a significant effect on the human development index. Open unemployment has a significant effect on the human development index. Government expenditure has a significant effect on the Human Development Index. Keywords: Economic Growth, Poverty Level, Government Expenditures, Open Unemployment Rate, and Human Development Index.